Putting teeth in the tiger improving the effectiveness of arms embargoes - Brzoska, Michael; Lopez, George A. (Contributions to conflict management, peace economics and development, 2009)
Foreign affairs practitioners and policy analysts claim that international arms embargoes usually fail due to the lack of political will among national governments to implement and enforce these restrictions. This title confronts this critique by describing an assessment of success